Analysis of Internal and External Factors of Pangandaran Beach’s Attractiveness for Foreign Tourists - Muhammad Rian Bajrah; Budi Harsanto (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Pangandaran Beach, a premier West Java destination, offers stunning beaches and rich culture, but it depends heavily on domestic tourists, with international visitors remaining minimal. This gap presents strong potential to enhance global appeal and support Indonesia’s tourism foreign exchange goals post-pandemic. This study aims to analyze the internal and external factors affecting Pangandaran Beach’s attractiveness to international tourists and assess their influence. A qualitative descriptive case study approach was employed. Data were gathered through in-depth interviews with purposively selected informants, field observations, and document review. Analysis used the six tourism components framework (attractions, accessibility, amenities, activities, available packages, ancillary services), along with internal factor evaluation, external factor evaluation, and SWOT matrices. Findings reveal a reasonably good internal condition (score 2.569) driven by natural beauty, unique geography, cultural richness, and friendly locals, though weaknesses persist in environmental management, accessibility, amenities quality, and service consistency. The external environment is moderately challenging (score 2.465), with opportunities from nature-culture tourism trends and low competition among Java beaches not yet fully leveraged against threats like degradation and inconsistent practices. Stronger governance, environmental care, better access and services, and stakeholder collaboration are essential to unlock sustainable international competitiveness, driving higher foreign revenue, jobs, and balanced regional tourism growth.